Avaliação do conhecimento e da presença de fatores de risco cardiovasculares de uma população de idosos do município de Cruz Alta-RS - Richter, Cleusa Maria (2011)
Brazil is getting older, the Census of 2010, we had more than 20.4 million seniors. The increase in longevity increases the importance of maintaining health and autonomy of this population, as advancing age, by itself, increases the risk of chronic non-communicable diseases, especially cardiovascular disease. Several studies indicate that the loco regional cardiovascular risk factors (CVRF) are prevalent in the elderly. Objective: To evaluate the level of knowledge that the elderly have on cardiovascular risk factors and the presence of this population of Cruz Alta-RS. Methods: A sample of 313 elderly (55.6% women) investigated the presence and knowledge of these through a structured questionnaire, including hypertension (HBP), hypercholesterolemia, diabetes mellitus (DM), hypertriglyceridemia, smoking, sedentary lifestyle, stress and family history of myocardial infarction (FH-MI), followed by objective assessment of CVRF, this step includes the measurement of blood pressure, anthropometric measures (weight, height, body mass index [BMI] and circumference abdominal [CA]) and laboratory tests. Results: The percentage of elderly connoisseurs CVRF were: hypertension in 95.2%, hypercholesterolemia in 95.5%, DM 97.7%, hypertriglyceridemia in 91.7%, alcohol in 97.4%, and smoking 99.7%. The presence of CVRF the elderly were: hypertension in 56.9%, hypercholesterolemia in 29.2%, DM 11.5%, hypertriglyceridemia in 16.6%, smoking in 11.5%, 63.6% in sedentary, stress in 49.8%, and FH-MI in 21.4%. Objective evaluation of CVRF met on average: systolic 138.6 ± 19.7 mm Hg, diastolic blood pressure 83.9 ± 12.3 mm Hg, BMI 27.4 ± 4.7 kg/m2; CA 97.7 ± 12.9 cm. The laboratory tests were obtained on average the following results: Total Cholesterol 208 ± 49.2 mg/dL, glucose 102.4 ± 28.8 mg/dL, triglycerides 151.7 ± 88.6 mg/dL. Conclusions: Elderly mostly proved to be knowledgeable of cardiovascular risk factors. However, the presence of risk factors was reported by a minority of the population, with the exception of hypertension, sedentary lifestyle and stress. This inverted ratio suggests that awareness of cardiovascular risk factors could reduce its prevalence